Hambatan Anak Mengikuti Pembelajaran Di Sekolah Minggu Pada Gereja Kristen Indonesia Klasis Sentani - Banga, Berthin Samuati; Roragabar, Yeni Irawati; Sarwuna, Adrianus (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2023)
This research examines the role of parents and the church in fostering children's motivation to participate in learning at Sunday School at the Sentani Klasis Indonesian Christian Church. The research method used is a combination of quantitative and qualitative methods. The procedure for collecting data is through questionnaires, interviews, and observation techniques. Research participants were parents and Sunday School teachers, as well as 30 Sunday School children. The research results show that children are strongly motivated to participate in Sunday School learning but face several obstacles. The first obstacle is the lack of parental support in technical matters and in providing motivation. The second obstacle is the church's lack of optimal efforts to facilitate learning in Sunday School, from the curriculum not yet being implemented to the lack of available learning tools to the teacher's lack of skills in using creative learning methods. Apart from that, parents and teachers have not communicated intensively regarding Sunday School learning. Therefore, so that Sunday School learning at GKI Klasis Sentani can run well and motivate children to be more active in participating in Sunday School learning, parents and the church need to increase their respective roles well.